The Effectiveness of Android-Based E-Comics in Improving Students' Understanding of Mixture Separation Concepts in Grade X Vocational High Schools - Popon Sucimiasih; Alizar Alizar (Jurnal Ilmu Pendidikan, 2025)
The purpose of this study is to ascertain how employing Android-based e-comics affects grade X vocational high school students' comprehension of the mixture separation concept. This study employs a quasi-experimental method with a quantitative approach, involving two groups: an experimental class using e-comics and a control class using conventional learning media. The research subjects were 10th grade students at SMKN 7 Kota Batam, while the object of research was students' conceptual understanding of mixture separation material. Data were collected using a conceptual understanding test administered before (pretest) and after (posttest) the treatment. Data analysis involved tests of normality, homogeneity, and an independent sample t-test to compare the posttest scores between the experimental and control groups. The results showed that the posttest scores of the experimental class were significantly higher than those of the control class, with an independent sample t-test result of t(78) = 9.042, p = 0.000 < 0.05, and a mean difference of 14.800. These findings indicate that the use of Android-based e-comics had a statistically significant positive effect on improving students' conceptual understanding.